A comparative analysis of knock severity in a Cooperative Fuel Research engine using binary gasoline–alcohol blends. (June 2021) - Corral-Gómez, Lis; Rubio-Gómez, Guillermo; Rodriguez-Rosa, David; Martín-Parra, Andrea; de la Rosa-Urbalejo, Daniel; Martínez-Martínez, Simón
Knock remains one of the main limitations for increasing the efficiency in spark-ignition engines. The use of certain alcohol–gasoline blends is an effective way to either mitigate or eliminate knock, allowing the use of higher compression ratios, therefore increasing the efficiency of spark-ignition engines. Methanol and ethanol are alcohols commonly employed for reducing knock, due to their higher octane number and vaporization heat value. Major attention is being paid recently to butanol and its blends with gasoline since they present similar characteristics to gasoline; however, it was found to be the least knock resistant among the three fuels. In the present work, a comparison between the knock performance of methanol–gasoline, ethanol–gasoline and butanol–gasoline blends is carried out, by volume concentrations up to 20 v/v%. This comparison is made in terms of knock intensity and knock probability. Tests are performed in a single-cylinder, variable-compression ratio, Cooperative Fuel Research engine equipped with port fuel injection system, facilitating the comparison against future results obtained by similar experimental facilities. Results obtained allow to reach meaningful conclusions about the capacity of each blend to mitigate knock.